(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Inclusive education means that all students attend and are welcomed by their neighbourhood schools in age-appropriate, regular classes and are supported to learn, contribute and participate in all aspects of the life of the school. Inclusive education is about how we develop and design our schools, classrooms, programs and activities so that all students learn and participate together. Inclusive education is carried out in a common learning environment that is, an educational setting where students from different backgrounds and with different abilities learn together in an inclusive environment. Inclusive education is about ensuring access to quality education for all students by effectively meeting their diverse needs in a way that is responsive, accepting, respectful and supportive. This paper identifies key concepts associated with inclusive education and discusses them in relation to issues such as lack of well-educated teachers, improper curriculum adaptation , learning environment in inclusive setting, resources, good infrastructural facilities, awareness, positive attitude, plans, socioeconomic factors, funding, policies which are creating hurdles for extending the concept of inclusive education in India. The objective of this paper is to point out the practices and challenges in the field of inclusive education in India.